PREDICTIVE ALGORITHM ANALYSIS FOR OPTIMAL PREVENTIONS IN TIME OF CORONAVIRUS (COVID-19) DURING QUARANTINE DAYS - Calderón Ch, J. Alan (2021)
This research explains the applications of the algorithm that was designed to provide statistical support for medical doctors. The support that was achieved from this research looks for an urgent interpretation of parameters such as the rate of infected people by COVID-19 and the rate of deceased people because of this virus. Furthermore, this research achieves prediction rates that were provided by a mathematical model that observes and adapts real statistical data from other countries, where governments are trying to find solutions against of COVID-19 propagation. It means, in order to get accuracy in prediction results, it was necessary to analyse what was the statistical behaviour from China and other countries that returned to normal activities as it was before virus imposed to confine population inside homes. On the other hand, it is summarized the virus problematic growth and some suggestions, how to avoid deep complications in health and economy of people (for instance, quarantine days as the main response to attenuate advance of this virus).